Determination of foot strike and toe-off event timing during maximal sprint using kinematic data - Nagahara, R.; Zushi, K. (International Journal of Sport & Health Science, 2013)
The aim of this study was to compare and validate a kinematic-based event detection method for a foot strike and toe-off during an accelerated sprinting. Five male sprinters ran 10, 15, and 25 m with maximal effort while a motion capture system collecting the positional data before the foot strike and after the toe-off at the 2nd, 6th, and 10th step. The ground reaction force at these steps was also recorded simultaneously. The foot strike was determined using the peak vertical acceleration of the markers on the toe and the first and fifth metatarsal head. The toe off was detected using the peak vertical acceleration and the lowest point of the marker on the toe. As a result, the method using the peak vertical acceleration of the marker on the toe for foot strike is sufficiently reliable and accurate for detecting the foot strike during an accelerated sprinting. For the toe-off, using the lowest point of the marker on the toe reliably and accurately detects event timing. As a conclusion, the foot strike and toe-off events for serial steps during accelerated sprinting on a ground or treadmill can be detected accurately using proposed kinematic-based methods.